Pharmacokinetic Prediction Of Apigenin From Celer (Apium Graveolens L.) Using Pkcsm - Lusiana Aprillia; Fendy Prasetyawan; Yuneka Saristiana; Ratna Mildawati; Chandra Arifin; Abd Rofiq (PT Pustaka Cendekia Publisher, 2025)
Celery (Apium graveolensL.) is a plant that has various pharmacological activities. One of the main bioactive compounds in celery is apigenin. Understanding the pharmacokinetic properties of apigenin is very important in evaluating its effectiveness and safety as a drug candidate. This study aims to predict the pharmacokinetic properties of apigenin using the pkCSM computational approach. The prediction results show that apigenin has good intestinal absorption, but low water solubility. Distribution ability is moderate, with limited penetration into the central nervous system. Apigenin is not a major substrate of CYP2D6 and CYP3A4 enzymes, but can inhibit CYP1A2 and CYP3A4. The elimination rate is moderate. Apigenin is not mutagenic, not hepatotoxic, and does not cause cardiotoxic effects. Apigenin has low toxicity toT. pyriformisand safe in acute doses with an LD50 of 2,432 log mM.